Antibiotic sensitivity of catheter-associated bacterial pathogens in pediatrics patients - Muhammad Aetesam Nasir; Falak sher; Ifrah Saroosh; Aisha Shakir; Muhammad Abdullah; Gull Zaman; Hira Ashiq; Muhammad Waqar Mazhar (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2023)
Antimicrobial-resistant (AMR) pathogens causing Urinary Tract infection is a serious public health concern in our clinical setting. A total of 200 catheter tips were collected from the different wards (medical, surgical, urology) at the Children's Hospital Faisalabad. Samples were streaked on nutrient agar plates and the positivity of the samples was noted after 24 hours. Positive samples were processed further for the identification of K. pneumoniae, P. aeruginosa, S. aureus, and E. coli using culture identification, microscopy, and biochemical profiling on the basis of culture characterization, microscopy, biochemical profiling, and antibiotic susceptibility testing. 76 (38%) of the samples showed growth on nutrient agar. In processed samples, the high prevalence was marked for P. aeruginosa (24/200; 12%) followed by E. coli (22/200; 11%) and S. aureus (19/200; 9.5%) while 11 K. pneumoniae isolates (5.5%) were identified in this study. In antibiotic susceptibility profiling of P. aeruginosa, the highest susceptibility was found for colistin (100%) and imipenem (70.83%) followed by gentamicin (54.17%) while the highest resistance was found for tobramycin (54.17%) followed by meropenem, ceftazidime, and cefotaxime (50%).  Conclusion: Advance studies are needed to investigate the real investigations of bacterial contamination; resistance to treatment options and resistance to antibiotics are needed.